1986
DOI: 10.1530/jrf.0.0770613
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urine from females in oestrus on puberty in female mice

Abstract: Summary. A series of 9 experiments was conducted to examine various characteristics of the urinary chemosignal found in the urine of oestrous female mice that accelerates the sexual development of conspecific females. This urinary chemosignal was effective in doses as small as 0\m=.\001 ml/day, was present in excreted and bladder urine, required 3 days of treatment starting before Day 29 of age to effect an acceleration of puberty, required a minimum daily exposure of 2 h, and was relatively nonvolatile. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…One set of external factors that affects the hormonal developmental program for some rodent species and thus may affect behavior development of the organism, involves a series of urinary chemosignals (Vandenbergh, 1983;Vandenbergh & Coppola, 1986;Drickamer, 1986a). These chemosignals have been investigated most thoroughly in house mice (Mus musculus domesticus) and include acceleration of puberty by urine from adult males, females in estrus, and females that are pregnant or lactating (Vandenbergh, 1969;Drickamer, 1986b;Drickamer & Hoover, 1979), and delay of puberty by a urinary signal from grouped females (Vandenbergh, Drickamer, & Colby, 1972;Drickamer, 1974Drickamer, , 1977. Similar effects involving urinary chemosignals and sexual development have been reported for other rodent species including voles (Microtus spp.…”
Section: Drickamermentioning
confidence: 99%
“…One set of external factors that affects the hormonal developmental program for some rodent species and thus may affect behavior development of the organism, involves a series of urinary chemosignals (Vandenbergh, 1983;Vandenbergh & Coppola, 1986;Drickamer, 1986a). These chemosignals have been investigated most thoroughly in house mice (Mus musculus domesticus) and include acceleration of puberty by urine from adult males, females in estrus, and females that are pregnant or lactating (Vandenbergh, 1969;Drickamer, 1986b;Drickamer & Hoover, 1979), and delay of puberty by a urinary signal from grouped females (Vandenbergh, Drickamer, & Colby, 1972;Drickamer, 1974Drickamer, , 1977. Similar effects involving urinary chemosignals and sexual development have been reported for other rodent species including voles (Microtus spp.…”
Section: Drickamermentioning
confidence: 99%
“…The findings from these experiments may be related to both the physiological mechanisms underlying the onset of puberty and the natural biology of house mice. Previous findings have indicated that the young female mice are affected by the duration of daily exposure to urinary chemosignals (Drickamer, 1983(Drickamer, , 1986a and that they are capable, for some of the chemosignals, of accumulating the effects of intermittent exposures to urine (Drickamer, 1987) through some as yet undetermined physiological mechanisms. The present investigation extends those findings by demonstrating that the physiological mechanisms that are responsible for recording the urinary chemosignals are also capable of quantitative discrimination.…”
Section: Table 9 Mean Age Of First Estrus In Female House Mice Treate...mentioning
confidence: 99%
“…Puberty in young female house mice ( Mus domesticus ) can be influenced by chemosignals contained in the urine of conspecifics (Drickamer, 1986b; Vandenbergh, 1983) and the effects of the changes in puberty may have consequences for the reproductive ecology of the mice (Bronson, 1979). Experimental treatments involving exposure of young females to urine from male mice, from female mice in estrus, and from female mice that are pregnant or lactating all lead to accelerated sexual development (Colby & Vandenbergh, 1974; Drickamer, 1986a; Drickamer & Hoover, 1979; Vandenbergh, 1969) whereas treatments involving exposure to urine from grouped female mice delay the onset of puberty (Drickamer, 1974; Vandenbergh, Drickamer, & Colby, 1972).…”
mentioning
confidence: 99%
“…There are at least 4 known urinary chemosignals that influence the timing of first vaginal oestrus in young female house mice. Urine from male mice, from oestrous female mice and from pregnant or lactating female mice all accelerate the onset of first oestrus (Vandenbergh, 1969; Colby & Vandenbergh, 1974;Drickamer & Hoover, 1979;Drickamer, 1986a), whereas urine from grouped females delays first oestrus (Vandenbergh et al, 1972;Drickamer, 1974Drickamer, , 1977). The pubertyaccelerating chemosignal in male mouse urine is androgen-dependent, being absent from the urine of castrated or prepubertal males, and reappearing when adult castrated males are given hormone replacement therapy (Colby & Vandenbergh, 1974;Lombardi & Vandenbergh, 1977;Drickamer & Murphy, 1978).…”
Section: Introductionmentioning
confidence: 99%